Audience Familiarization and Self-Calming Strategies in Managing Public Speaking Anxiety - Nelson U. Julhamid; Raugda J. Julhamid (Environment and Social Psychology, 2025)
Public speaking anxiety remains a common challenge across academic and professional settings, yet limited research has examined how speakers use audience familiarization and self-calming strategies to manage this anxiety. This qualitative exploratory study investigated (1) how individuals perceive and experience familiarizing themselves with audiences, and (2) the self-calming techniques they employ to regulate their anxiety during public speaking. Semi-structured interviews were conducted with 18 public speakers, and Reflexive Thematic Analysis (RTA) was used to identify patterns in their experiences. Findings show that audience familiarization—through demographic research, cultural awareness, and pre-speech interpersonal interactions—reduces uncertainty and fosters a sense of connection, thereby easing anxiety. Participants also used self-calming strategies such as deep breathing, visualization, positive affirmations, and tension-release exercises to manage physiological and cognitive symptoms of nervousness. Together, these strategies helped normalize anxiety and enhanced speakers’ confidence and self-trust over time. The study offers practical recommendations for education and training. Integrating audience analysis activities, mindfulness-based calming techniques, and supportive presentation environments into communication curricula can help students and emerging professionals build stronger speaking competence and emotional resilience. These findings highlight the value of a holistic approach that combines external preparation with internal regulation to effectively manage public speaking anxiety and improve speaker performance.